Serum osteopontin and vitronectin levels in systemic sclerosis - Gundogdu, Baris; Yolbas, Servet; Yilmaz, Musa; Aydin, Suleyman; Koca, Sulayman Serdar (Wroclaw Medical Univ, 2017)
Background. Osteopontin a matricellular protein has pro-fibrotic effects and binds integrin such as av beta 1 and av beta 3. Vitronectin is one of the integrin av beta 3 ligands and is a multifunctional glycoprotein. Objectives. The aim of the present study was to evaluate serum osteopontin and vitronectin levels in a cohort of patients with systemic sclerosis (SSc). Material and methods. Eighty-six patients with SSc, 46 patients with systemic lupus erythematosus (SLE), and 38 healthy controls (HC) were enrolled in the study. Serum osteopontin, vitronectin, IL-6, and TGF-beta levels were analyzed. Results. Serum osteopontin levels were higher in the SSc and SLE groups compared to the HC group (p < 0.01 and p < 0.001, respectively). However, it was not correlated with disease activity and severity scores in the SSc group. On the other hand, serum vitronectin levels were lower in the SSc group than in the SLE and HC groups (p < 0.001 for both). Conclusions. These results may suggest that osteopontin levels may be increased due to the inflammatory process and osteopontin has not a specific role on fibrosis in SSc. On the other hand, serum vitronectin levels decrease in SSc in contrast to SLE. It may be concluded that the one cause of decreased serum vitronectin levels in SSc may be its accumulation in fibrotic area.
Keywords: systemic sclerosis; osteopontin; vitronectin